How is the Rural Industrial Development Project performing? - Budget Monitoring and Accountability Unit (Budget Monitoring and Accountability Unit, 2019)
A strong and competitive industrial sector is important to create employment, advance technology and create a resilient economy. As one of the initiatives to achieve industrialization, the Ministry of Trade, Industry and Cooperatives (MoTIC) is implementing a five-year Rural Industrial Development Project, a successor to the One Village One Product project that ended in FY 2016/17. The overall objective of the project is enhancing access to value addition and collective marketing infrastructure for improved competitiveness and productivity of rural enterprises. The RIDP aims at promoting value addition to agricultural products at different levels of the commodity value chain that include drying, storage, preservation, packaging, processing and certification. This will be achieved through promotion of production and industrial processing clusters. These include operators of the storage facilities, suppliers of raw materials for processing, value addition enterprises, manufacturers and distributors of value addition equipment and providers of business development services. The success of the project will be evaluated basing on the degree of realization of the targeted outputs and outcomes for which it is designed. This policy brief assesses the effectiveness of the Industrial and Technological Development Programme with specific focus on the Rural Industrial Development Project. It identifies implementation challenges and proposes policy recommendations.